Perancangan Antena Mikrostrip Circular Dual-Band 28 Dan 38 Ghz Dengan Metamaterial Crlh (Composite Right Left Handed) Untuk Jaringan Komunikasi 5g - Firman Robiansyah; Yusnita Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
In recent years, the development of fifth generation (5G) communication technology has become an interesting issue. It is a new communication that improve network efficiency, capacity data rate and lower power consumption. In this paper , a circular metamaterial composite right left handed microstrip antenna is designed. The antenna is simulated by using CST microwave studio operated at 28/38 Ghz. The substrate used is RT Duroid 5880. From the simulation result, the return loss of -36.932 dB and -32.977 dB are obtained for 28 GHz and 38 GHz bandwidth of 7.68 GHz and 6.41 GHz and gain-of 4.91 dB and 5.2 dB. Keyword:Metamaterial CRLH, Microstrip antenna, 5G antenna